Ba4(BS3S)2S4: a new thioborate with unprecedented [BS3-S] and [S4] fundamental building blocks. Issue 98 (25th November 2019) - Li, Guangmao; Li, Junjie; Wu, Kui; Yang, Zhihua; Pan, Shilie
Abstract : The first BS-S group, BS3 S, with π-conjugation composed of planar BS3 and a non-polar covalent S–S bond. Abstract : Ba4 (BS3 S)2 S4 with unprecedented [BS3 -S] and [S4 ] units has been synthesized successfully. The [BS3 -S] unit named as (disulfido)bis(sulfido)borate(3-) is composed of a planar [BS3 ] group with a non-polar covalent S–S bond and stabilized by a large π-conjugation structure. The [S4 ] unit, formed by four S atoms, shows a helix chain-like structure. This work will enrich the structural diversity of boron chemistry.